Effect of nano-silica on the mechanical properties of LWC - Nashat, Alghrairi; Abd Aziz, Farah Nora Aznieta; Abdul Rashid, Suraya; Mohamed, Mohd Zuhri; Mohammed Ibrahim, Amer (Walter de Gruyter GmbH, 2024)
Nanotechnology has made significant inroads across various sectors, augmenting properties and economic impacts. Its pivotal role extends notably to the realm of construction and building. This study focuses on the tangible consequences of incorporating nano-silica (NS) into lightweight concrete (LWC) and its influence on mechanical attributes. The primary aim is to illustrate how NS impacts the mechanical properties of LWC, specifically its effects on compressive strength, flexural strength, and tensile strength in comparison to conventional LWC. The research encompassed the casting and examination of seven distinct concrete mixtures, including a reference mix, in laboratory settings. The study findings highlight that the utilization of lightweight Iraqi porcelanite stone resulted in a one-third reduction in the weight of standard concrete. Furthermore, the introduction of varying quantities of NS into structural LWC yielded enhancements in compressive, tensile, and flexural strength when contrasted with the reference mix, albeit at the expense of workability. Remarkably, The results showed an introduction of varying quantities of NS into structural LWC yielded enhancements in compressive, tensile, and flexural strength when contrasted with the reference mix, albeit at the expense of workability. The findings demonstrated that when doses of 1, 3, 5, 10, 15, and 20% NS were applied, the rate of three models for determining compressive strength at 90 days old rose by 19, 45, 62, 32, 15, and 37%, respectively. On the other hand, when dosages 1, 3, 5, 10, 15, and 20% were added, the percentage of improvement in tensile strength at 28 days of age was 77, 75, 84, 51, 55, and 53%. Additionally, while employing the same above doses, the bending strength at 28 days of age improved by 141, 140, 171, 115, 114, and 108%, respectively. Remarkably, the results also underscored the sustained efficacy of NS, particularly during the later stages of concrete maturation. © 2024 the author(s)